Handbook of porous media - Vafai, K. (CRC Press, Taylor & Francis Group, 2015)
Handbook of Porous Media, Third Edition offers a comprehensive overview of the latest theories on flow, transport, and heat-exchange processes in porous media. It also details sophisticated porous media models which can be used to improve the accuracy of modeling in a variety of practical applications.